Children's physical activity during a segmented school week: results from a quasi-experimental education outside the classroom intervention - Mikkel Bo Schneller; Jasper Schipperijn; Glen Nielsen; Peter Bentsen (BMC, 2017)
Abstract Background Movement integration (MI) into traditional classroom teaching is a promising opportunity for children to increase physical activity (PA). Education outside the classroom (EOtC) can be regarded as MI, and has increased children's PA in case studies. The aim of this study is to investigate the effects of EOtC on children's PA by segmenting weekly activity-related behavior into a range of day types and domains. Methods In a quasi-experimental design, 33 classes were recruited and participants' PA was objectively measured using accelerometers taped to the lower back. In total, 361 (10.89 ± 1.03 years) participants with 7 days of 24 h wear time per day were included in a day type PA analysis, and 194 of these participants (10.46 ± 0.99 years) provided information on time spent in specific domains (e.g. EOtC or recess) and were included in a domain-specific PA analysis. Differences in proportion of time spent in PA intensities were tested using mixed-effects regression models. Results More moderate-to-vigorous physical activity (MVPA) occurred on days with physical education (PE) than days with EOtC (girls 0.79%, p = .001, CI = .26% to 1.31%; boys 1.35%, p = .003, CI = .32% to 2.38%), while no difference was found between EOtC days and school days without EOtC and PE. Light physical activity (LPA) was higher on EOtC days than school days without EOtC and PE (girls 2.43% p < .001, CI = 1.21% to 3.65%; boys 2.08%, p < .001, CI = .69% to 3.47%) and PE days (girls 2.18%, p < .001, CI = .80% to 3.56%; boys 2.40%, p < .001, CI = .83% to 3.96%). Comparing EOtC and classroom domains, boys proportionally spent 7.95% (p < .001, CI = 3.00% to 12.90%) more time in MVPA while no difference (p = 1.000) was measured for LPA, and girls had no difference (p = .176) in MVPA, but spent 9.76% (p < .001, CI = 7.12% to 12.41%) more time in LPA. Conclusions EOtC was implemented without the provision of additional resources and with positive effects on PA. Findings suggest EOtC as a way to provide children with an additional opportunity to accumulate PA within the existing school setting.